If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-2y + 3) = 0 Reorder the terms: 7(3 + -2y) = 0 (3 * 7 + -2y * 7) = 0 (21 + -14y) = 0 Solving 21 + -14y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + -14y = 0 + -21 Combine like terms: 21 + -21 = 0 0 + -14y = 0 + -21 -14y = 0 + -21 Combine like terms: 0 + -21 = -21 -14y = -21 Divide each side by '-14'. y = 1.5 Simplifying y = 1.5
| 14+-2x=-3(x+1)-5 | | 55x+5y=45 | | 4(2x+5)+3x-2(x-7)=3(2x+7)-8 | | [Y]=5 | | -3x-2y=-2 | | 3(z-1)= | | 14-2x=-3(x+1)-5 | | 6(3+1)-30=3(2n-4) | | -6y+2y=-104 | | 4x-3+3=12 | | 9x-7=4x+9 | | 3x^2-5x+5=33 | | 10x-35+3x=5x-7a | | N+11=2 | | 2(3+x)=14x | | 11(4-3x)-5(2x+13)=194 | | -2y-42=-4(y+7) | | -2(y+9)= | | 5(c+2)=25 | | .4(12n-8)=26 | | 4(2x-7)=3(x+4) | | 2b+12b=70 | | 13x+(x+3)+(x+2)+(x+7)=40 | | 6x^3-5x^2+1=0 | | -3x-14+10x=-2 | | -6(v+7)=9v+48 | | 2(3x+8)+6(x-1)=-12 | | 5x-4+3x=6x+4(2-x) | | 8-5x=-29 | | (5n^2+11)-(3n^2+6)= | | -3.4m=47.6 | | -7x+30=-5(x-8) |